Comparation in the use of verb, article, prepositions, and clitics pronouns in schoolers with developmental language disorder (DLD) and typical development (TD) - Chaf Gallardo, Gabriela Viviana; Julia Coloma , Carmen; Quezada , Camilo (Revista de Investigación en Logopedia, 2023)
The present study aims at inspecting grammatical performance of monolingual Spanish-speaking schoolers diagnosed with DLD. They were all first-graders living in Santiago, Chile. Verbs, articles, prepositions, and pronouns were examined, elicited by means of a retelling task based on three short stories. Two groups were observed. The first group consisted of 30 first-graders with DLD (mean age 6 years 8 months). The second group consisted of 30 first graders with Typical Development (TD, mean age 6 years 9 months). Results showed that children with DLD produce less verbs, prepositions and proclitics. When examining errors, children with DLD were found to make significantly more mistakes that children with TD. When comparing errors for verbs, prepositions, and proclitics among children with SLI, no differences were observed. As for articles, both groups exhibit similar patterns. Enclitics were rarely used by children, regardless of observed group. Among children with SLI, the most frequent error, regarding prepositions and pronouns, was omission.